2010
DOI: 10.1016/j.psyneuen.2010.04.008
|View full text |Cite
|
Sign up to set email alerts
|

No association between oxytocin or prolactin gene variants and childhood-onset mood disorders

Abstract: Background-Oxytocin (OXT) and prolactin (PRL) are neuropeptide hormones that interact with the serotonin system and are involved in the stress response and social affiliation. In human studies, serum OXT and PRL levels have been associated with depression and related phenotypes. Our purpose was to determine if single nucleotide polymorphisms (SNPs) at the loci for OXT, PRL and their receptors, OXTR and PRLR, were associated with childhood-onset mood disorders (COMD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 65 publications
0
11
1
Order By: Relevance
“…The SNP rs237885 was reported to be associated with overall symptom severity in schizophrenia (Souza et al 2010a) and prosocial decision making (Israel et al 2009), but was not implicated in childhood mood disorder (Strauss et al 2010), ADHD (Park et al 2010) or autistic symptoms (Chakrabarti et al 2009;Tansey et al 2010). However, lack of signifi cance in our study may also be due to limited statistical power.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The SNP rs237885 was reported to be associated with overall symptom severity in schizophrenia (Souza et al 2010a) and prosocial decision making (Israel et al 2009), but was not implicated in childhood mood disorder (Strauss et al 2010), ADHD (Park et al 2010) or autistic symptoms (Chakrabarti et al 2009;Tansey et al 2010). However, lack of signifi cance in our study may also be due to limited statistical power.…”
Section: Discussionmentioning
confidence: 58%
“…The C-allele of OXT 3 ' SNP rs2740210 was reported to be overtransmitted in childhood-onset mood disorder (Strauss et al 2010). OXTR intron 3 SNP rs53576 was implicated in several studies of phenotypes with social or emotional dysfunction (Wu et al 2005;Costa et al 2009;Israel et al 2009;Lucht et al 2009;Rodrigues et al 2009;Park et al 2010;Souza et al 2010a).…”
Section: Participantsmentioning
confidence: 99%
“…DNA extraction and genotyping were carried out at the Center for Addiction and Mental Health (CAMH), Toronto, ON, Canada. Because of the relative lack of known functional polymorphisms in the two candidate genes, particularly the OXT peptide gene, we chose the SNPs based on available evidence of associations with mood disorders (Strauss et al 2010), antipsychotic treatment response (Souza et al 2010) and maternal behavior, including maternal care and vocalizations to the infant (Mileva-Seitz et al 2013). Furthermore, there is evidence that the OXTR SNP in this study (rs237885) is part of a haplotype block for OXTR, which is significantly associated with prosocial behaviors (Israel et al 2009;Saphire-Bernstein et al 2011).…”
Section: Buccal Cell Swabs and Genotypingmentioning
confidence: 99%
“…Other studies, however, report no association between the OXTR rs53576 G-allele and prosocial effects (Cornelis et al, 2012;Kawamura et al, 2010) (see for a meta-analysis Bakermans-Kranenburg and van IJzendoorn, 2014). Little is known about the influence of OXTR rs53576 on major depression: two studies reported no significant relationship between OXTR rs53576 genotypes and childhoodonset mood disorders (Strauss et al, 2010) or treatment outcome in depressed patients (Mendlewicz et al, 2012). Studies including environmental factors suggested that homozygote G-allele (GG) carriers may be at higher risk for depression (Costa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%